Yeast Quality Distribution in the Cone of Cylindro Conical Tanks - Thiele, Frithjof; Hartwig, Axel; Back, Werner (BrewingScience, 2008)
Yeast cropping from cylindro-conical tanks and repitching of the yeast is a key procedure in the brewing industry. In general it is assumed that the yeast collected from the cone of a tank is a homogenous culture. However results from studies investigating this aspect indicate that yeast quality as well as the environmental conditions within the cone can vary extensively. Results from different studies have been contradictory in various aspects. In order to add more information to this topic several yeast crops in two industrial breweries were followed obtaining samples in certain intervals. Each sample was analyzed for the physiological conditions of the yeast and various characteristics of the recoverable beer were investigated. In addition for some trials the replicative age and the fermentation performance in EBC Tall tubes have been examined. It was found that yeast vitality and viability did not vary considerably throughout the individual crops but large differences were found in-between several crops. Similar results were found for the characteristics of the recoverable beer. Regarding the replicative cell age a gradient throughout the crop was found. But the fermentation performance of the individual samples could not be related to the cell age.